1992
DOI: 10.1104/pp.100.1.191
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dark Respiration between C3 and C4 Plants

Abstract: Lower respiratory costs were hypothesized as providing an additional benefit in C4 plants compared to C3 plants due to less investment in proteins in C4 leaves. Therefore, photosynthesis and dark respiration of mature leaves were compared between a number of C4 and C3 species. Although photosynthetic rates were generally greater in C4 when compared to C3 species, no differences were found in dark respiration rates of individual leaves at either the beginning or after 16 h of the dark period. The effects of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 28 publications
(38 reference statements)
5
35
1
Order By: Relevance
“…Elevated C, did not inhibit the alternative oxidase. The levels of inhibition obtained in soybean cotyledon mitochondria matched those reported for soybean leaves and whole plants by doubling ambient levels of C, (Bunce, 1990;Byrd et al, 1992;Thomas and Griffin, 1994).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Elevated C, did not inhibit the alternative oxidase. The levels of inhibition obtained in soybean cotyledon mitochondria matched those reported for soybean leaves and whole plants by doubling ambient levels of C, (Bunce, 1990;Byrd et al, 1992;Thomas and Griffin, 1994).…”
Section: Discussionsupporting
confidence: 67%
“…A reversible inhibition of CO, evolution by Rumex crispus leaves was observed when C, was increased stepwise through the range of O to 1000 pL L-' (Amthor et al, 1992). Inhibition of respiration by increasing C, has also been reported in whole plants (Bunce, 1990;Ryle et al, 1992), leaves (Reuveni and Gale, 1985;Bunce, 1990;El Kohen et al, 1991;Amthor et al, 1992;Byrd et al, 1992;Thomas and Griffin, 1994;Ziska and Bunce, 1994), roots (Reuveni and Gale, 1985;Palta and Nobel, 1989;Qi et al, 1994), microorganisms (Koizumi et al, 1991), and animal tissues (Palet et al, 1991). Respiration can also be unaffected or even increased when C, increases (Palet et al, 1991;Ryle et al, 1992).…”
mentioning
confidence: 87%
“…Based on these, the calculated respiration for protein turnover from the present work equates to 3n5-8n2 % and 6n3-14n5 % of total maintenance respiration, respectively, for 1 and 8 mol m −$ N-supplied plants. Similar calculations based on the data of Byrd et al (1992) for C $ and C % species with leaf N content comparable to that of the 8 mol m −$ N-supplied plants from the present work, also show respiration for protein turnover to be c. 3-20 % of total maintenance respiration. These results generally agree with those reported by Byrd et al (1992) and Amthor (1994), in that respiration due to protein turnover is not a major component of maintenance respiration.…”
Section: Effect Of Protein Turnover On the C Balance Of Plants And Itsupporting
confidence: 63%
“…Similar calculations based on the data of Byrd et al (1992) for C $ and C % species with leaf N content comparable to that of the 8 mol m −$ N-supplied plants from the present work, also show respiration for protein turnover to be c. 3-20 % of total maintenance respiration. These results generally agree with those reported by Byrd et al (1992) and Amthor (1994), in that respiration due to protein turnover is not a major component of maintenance respiration. Similarly, van der Werf et al (1992) found that, in the roots of Dactylis glomerata, a mere 4-7 % of the total energy production was used by protein turnover.…”
Section: Effect Of Protein Turnover On the C Balance Of Plants And Itsupporting
confidence: 63%
See 1 more Smart Citation